The Development of Problem Solving Skills through Problem-Based Learning in Economics in School Course - Montha Chumsukon (Faculty of Teacher Training and Education, Universitas Terbuka, 2019)
Problem-solving was necessary skill during the 21st century. According to the advanced social change, the traditional knowledge management focusing on the lecture which did not facilitate the problem thinking skill. The problem-based knowledge management was the instructional model, which could enhance the students’ problem-solving skill. The objectives of this research were: 1) to develop students’ problem-solving skill by using the Problem-Based Learning in Economics in School Course so that not less than 70% of students would have scores passing the specified criterion 70% of full score, and 2) to study the students’ satisfaction on Problem-Based Learning in Economics in School Course. The target group of this study was 32 second-year students who enrolled in Learning in Economics in School Course during the first semester of the 2017 academic year. There were 3 kinds of research instrument: 1) the instrument using for action including 9 problem-based plans, 27 hours, 2) the instrument using for reflecting research findings including the teachers’ teaching behavioral observation, the students’ learning behavioral observation, and 3 essay items of evaluation form in problem-solving skill at the end of cycle, and 3) the instrument used for evaluating the action performance including 5 multiple choice items of problem-solving skill, and 15 items of 5 level of rating scales for evaluating the students’ satisfaction. Data were 2 it is analyzed by using the statistics including percentage, mean, and standard deviation. The research findings found that: For the students’ problem-solving skill through problem-based learning in Economics in School Course, there were 25 students or 78% passing the specified criterion out of 32 students who were higher than the specified standard 70%. Also, the mean score was 42.7 9 points or 71.33% out of 60 points, passing the specified criterion 70%. For the students’ satisfaction in problem-based learning in Economics in School Couse, in overall, it was in “High” level (Very Satisfied). This research was classroom action research. It is beneficial for improving social studies teachers to develop future students. The students can continuously learn by themselves; it allows them the opportunity to achieve the goal of life-long learning and to become a person of quality for the 21st century.